FAIR Data for Energy System Research - Wein, Amanda; Reinkensmeier, Jan; Weidlich, Anke; Lilliestam, Johan; Hagenmeyer, Veit; Richter, Mascha; Auer, Sören; Nieße, Astrid; Lehnhoff, Sebastian (1st Conference on Research Data Infrastructure (CoRDI) - Connecting Communities, 2023)
The NFDI4Energy consortium aims to establish new services filling a variety of needs for the energy system research community, from making FAIR research data easily accessible to promoting collaboration among community entities. Seven Task Areas (TAs) have been defined to achieve the consortium’s objectives, each with a specific focus. Task Area 4 (TA4): FAIR Data for Energy System Research shall develop ontologies, metadata standards, and services to promote semantic consistency and improve interoperability of energy research projects, thereby supporting the harmonization of data management among various institutions and research field